2015
DOI: 10.1063/1.4928517
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic excitation-assisted optical and electric enhancement in ultra-thin solar cells: the influence of nano-strip cross section

Abstract: The effects of Ag nano-strips with triangle, rectangular and trapezoid cross sections on the optical absorption, generation rate, and short-circuit current density of ultra-thin solar cells were investigated. By putting the nano-strips as a grating structure on the top of the solar cells, the waveguide, surface plasmon polariton (SPP), and localized surface plasmon (LSP) modes, which are excited with the assistance of nano-strips, were evaluated in TE and TM polarizations. The results show, firstly, the TM mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the recent years, applying dielectric photonic crystals [3] and periodically patterned metallic structures [11] as back reflectors in order to enhance the electromagnetic energy intensity even beyond 4n 2 limit has become a popular trend. Using the plasmonic excitations in the ultra-thin solar cells, one can simultaneously increase the efficiency of solar cells and reduce the cost of film deposition [1,4,[12][13][14][15][16][17][18] which are two favorite factors in experimental research. Using perovskite-hybrid plasmonic nanostructured, Zhang et al have explained the role of plasmonic coupling and photonic cavities in enhancing light-matter interactions and manipulating carrier dynamics [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, applying dielectric photonic crystals [3] and periodically patterned metallic structures [11] as back reflectors in order to enhance the electromagnetic energy intensity even beyond 4n 2 limit has become a popular trend. Using the plasmonic excitations in the ultra-thin solar cells, one can simultaneously increase the efficiency of solar cells and reduce the cost of film deposition [1,4,[12][13][14][15][16][17][18] which are two favorite factors in experimental research. Using perovskite-hybrid plasmonic nanostructured, Zhang et al have explained the role of plasmonic coupling and photonic cavities in enhancing light-matter interactions and manipulating carrier dynamics [19].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate systematically the cell's performance, the optical absorption and short-circuit current density enhancements and resistive (Ohmic) loss of G-SiO 2 -Si-SiO 2 solar cells are calculated and compared with those of Ag nanostrips incorporated SOI (Ag-SiO 2 -Si-SiO 2 ) cells. For Ag-SiO 2 -Si-SiO 2 solar cells, the optimum design which has been reported previously [17,18] is used. For G-SiO 2 -Si-SiO 2 cells, width and the period of GNRs, which are two key parameters in the performance of proposed structure, are optimized.…”
Section: Introductionmentioning
confidence: 99%
“…S5†) for the TE polarized incident light, it is clear that the TM polarized modes provide stronger absorption enhancements, as reported in literature. 39–41 For smaller NPs, lower-order localized surface plasmon modes contribute to the trapped electric field whereas higher-order modes are excited by the larger NPs, coupling more light into the underlying c-Si absorber layer. 30 Simulation results show maximum electric field confinement around the near bandgap wavelength of λ = 1200 nm, when d Au = 40 nm, which is consistent with the absorption enhancement results displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is because previous studies have shown stronger plasmonic excitations in the TM mode providing higher absorption enhancements, leading to higher carrier generation rate and higher short circuit current density in plasmon enhanced solar cells. [39][40][41] To delineate this difference between TM and TE modes, the electric eld patterns are evaluated for both the modes where the polarization angles for the TE incident wave are set to 90°. The electric eld proles are obtained by placing a two-dimensional eld and power monitor in the xz plane through the centre of the parabola unit cell (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation